Development of Canva-Based Animation E-Mind Mapping Guide - Hasriadi Hasriadi; Firman Firman; Ningrum Ningrum (South Sulawesi Education Development (SSED), 2023)
Online learning in the context of the pandemic and digital age demands innovation in learning approaches. The transformation from face-to-face learning directly (offline) to virtual face-to-face (online) raises concerns about declining student learning quality. The study responded to this challenge by designing a Canva-based animated e-mind mapping guide as an innovative solution to improve students' understanding of online learning. This research adopts the ASSURE model teaching material development design involving 111 students of the Faculty of Tarbiyah and Teacher Training IAIN Palopo. This guide is designed to meet the needs of students with kinesthetic and visual learning styles. Involving teaching material experts, learning media experts, course lecturers, and students, this research uses validation sheets, questionnaires, and learning outcome test instruments. Data analysis involves qualitative techniques, descriptive statistics, and inferential T-tests to measure differences in learning outcomes before and after using guidelines. The results showed that Canva-based animated e-mind mapping guides effectively improved student understanding. The validity of this guide was confirmed through positive evaluations from validators and positive feedback from students and lecturers. Student performance assessment and pretest-posttest tests support the effectiveness of this method in supporting the learning process. The success of this guide highlights the importance of innovation and adaptation in education in the digital age, creating engaging, interactive, and efficient learning. This research contributes to students' understanding of online learning and inspires other educational institutions to adopt similar approaches in addressing today's educational technology challenges.